The state system of coordinates in the field of geodesy in the Republic of Kazakhstan and its current state - Akhanova U.B. Аханова У.Б. (Рroblems of engineering and professional education, 2023)
This article presents the theoretical background of building the satellite geodetic network and the establishment of a unified state system of coordinates on the territory of the Republic of Kazakhstan